Progressive loss of CD44 gene expression in invasive bladder cancer. - Sugino, T. (1996)
This study investigated CD44 gene expression at both the RNA and protein level in well differentiated superficial and in deeply invasive bladder carcinomas. Proteins were studied by immunohistochemistry using antibodies against standard (CD44s) and variant (CD44v) isoforms. mRNA was analyzed by reverse transcriptase polymerase chain reaction/Southern blotting and in situ hybridization. Immunostaining with antibodies against CD44s and CD44v2, -5 and -6 (exons 7, 10, and 11, respectively) showed that carcinoma cells in all papillary tumors expressed strong signals throughout the epithelium but especially in the basal layer, which abuts on the stroma. However, invasive tumors, which are believed to originate mainly from flat urothelial tumors or, less frequently, from papillary carcinomas, progressively lost CD44 proteins as they penetrated deeper and became less differentiated. This change was paralleled at the mRNA level, by the gradual loss of expression of CD44s and CD44v transcripts in deeply invasive tumors until they were virtually undetectable. Conversely, papillary tumors contained multiple higher molecular weight transcripts, suggesting that the loss of CD44 proteins in the more aggressive tumors is due to a disturbance in transcription. This concept was confirmed by in situ hybridization studies with a probe showing that substantial variant CD44 mRNA is located in the urothelium in papillary carcinomas but is absent from deeply invasive carcinomas. These results indicate that initially there is a striking increase in CD44 gene expression in early bladder carcinomas, relative to normal urothelium, but that this diminishes as the tumors acquire a more aggressive phenotype.